دراسة إحصائية للأمراض النباتية والمعالجة الحشرية المناسبة من حيث المساحة والجرعات - خزان, مروة; غنايم, سليمة (جامعة الوادي - University of Eloued, 2022)
The field study is some what minar in our academic lidraries, and the libraries , and the library is lacking Arabic in general to such field studies that follow most of the descriptive approach the and end Using the analytical and dexriptive approach, in which mathematical statistics and data transformation were introduced dexriptive data into quantitative data that can be processed, tabulated, and corresponding questionnaires drawn, We include appropriate tools and methods of analysis, interpretation of data and results, and analysis there of, including It serves the interests of the researcher, user , appraiser and scientific research , especially if the sciences are They interact with each other as a research method in mathematical statistics that improves the rest of the research Especially in the field, giving a new color and revising and improving its results for the better So that the observation, significance and statistical indicator have a material explanatory value It is effective in making the right decision and interpreting and analyzing the results according to a scientific method Descriptive analysis. Our choice fell on the Oued souf area of the district of botatos where the engages in activities Variety, which made the ecosystem slightly damaged by the intervention of the sponsor And the expert where to put the touches of chemical treatment conservatively , and that is where and that is between ,space and disease. We chose the Hassi khalifa region (as a model) .
التنوع الحيوي وفيزولوجيا النبات
Keywords: Maladies des plantes; traitement des insectes; أمراض النباتية ، المعالجة الحشرية